2019
DOI: 10.1002/ange.201910397
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselektive C(sp3)‐C(sp2)‐Kreuzkupplungen von chiralen sekundären Alkylzinkreagenzien mit Alkenyl‐ und Arylhalogeniden

Abstract: Wir berichten über Palladium‐katalysierte Kreuzkupplungsreaktionen von chiralen sekundären nicht‐stabilisierten Dialkylzinkreagenzien – hergestellt aus einfach verfügbaren chiralen sekundären Alkyliodiden – mit Alkenyl‐ und Arylhalogeniden. Mit dieser Methode wurden α‐chirale Alkene und Arene mit sehr hoher Retention ihrer Konfiguration (dr bis zu 98:2) und guter Gesamtausbeute (bis zu 76 % über 3 Reaktionsschritte) hergestellt. Die konfigurationelle Stabilität dieser chiralen nicht‐stabilisierten Dialkylzinkr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Furthermore, the functional group tolerance was limited and the scale‐up of these reaction sequences proved to be difficult affording poor yields and low optical purities. Thus, we have found that an in situ quench (ISQ, also known as Barbier conditions) [9] of chiral alkyl iodides in the presence of a suitable magnesium reagent with t ‐BuLi allowed the performance of the I/Li‐exchange at up to −50 °C with high stereoretention (up to 99 %) providing, upon transmetalation, several chiral secondary Grignard reagents [10] . Yet, the resulting chiral alkylmagnesiums proved to be unreactive towards some important classes of electrophiles ( 3 ) including enolizable or sterically hindered ketones.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the functional group tolerance was limited and the scale‐up of these reaction sequences proved to be difficult affording poor yields and low optical purities. Thus, we have found that an in situ quench (ISQ, also known as Barbier conditions) [9] of chiral alkyl iodides in the presence of a suitable magnesium reagent with t ‐BuLi allowed the performance of the I/Li‐exchange at up to −50 °C with high stereoretention (up to 99 %) providing, upon transmetalation, several chiral secondary Grignard reagents [10] . Yet, the resulting chiral alkylmagnesiums proved to be unreactive towards some important classes of electrophiles ( 3 ) including enolizable or sterically hindered ketones.…”
Section: Methodsmentioning
confidence: 99%
“…Außerdem war die Toleranz gegenüber funktionellen Gruppen begrenzt, und das Hochskalieren dieser Reaktionssequenz erwies sich als schwierig, was in geringer Ausbeute und geringer optischer Reinheit resultierte. Kürzlich berichteten wir, dass ein in situ Quench (ISQ, auch bekannt als Barbier‐Bedingungen) [9] von chiralen Alkyliodiden in Gegenwart eines geeigneten Magnesiumreagenzes mit t ‐BuLi die Durchführung des I/Li‐Austauschs bei bis zu −50 °C mit hoher Stereoretention (bis zu 99 %) ermöglichte und nach der Transmetallierung mehrere chirale sekundäre Grignard‐Reagenzien lieferte [10] . Die resultierenden chiralen Alkylmagnesiumreagenzien erwiesen sich jedoch als unreaktiv gegenüber einigen wichtigen Klassen von Elektrophilen ( 3 ), einschließlich enolisierbaren oder sterisch gehinderten Ketonen.…”
Section: Methodsunclassified